PENERAPAN MEDIA KADO RAGAM (KARTU DOMINO KEBERAGAMAN) UNTUK MENINGKATKAN HASIL BELAJAR PENDIDIKAN PANCASILA SISWA KELAS V SDN 3 RENON - I Nyoman Sudianta; Dewa Bagus Sanjaya; I Nengah Suastika (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the improvement of Pancasila learning outcomes of fifth grade elementary school students using Kado Ragam (Diversity Domino Cards) media. This research method is quantitative descriptive, with the type of classroom action research using two cycles. Data collection of student learning outcomes using multiple choice tests. The subjects of this study were 30 fifth grade students of SDN 3 Renon Denpasar. Based on the data from the research results of cycle I. obtained KKTP 70, average value 70.17, highest value 90, lowest value 50, absorption power 70.17% and percentage of learning completion 58.62%, with data on students who completed 17 people and did not complete 13 people, because the percentage of learning completion is still below 80%, the research was continued in cycle II. The results of the cycle II research showed an average value of 81.83, the highest value of 95, the lowest value of 60, absorption power of 81.83% and the percentage of learning completion of 86.21%, with student data that completed 26 people completed and 4 people did not complete and the research was stopped. The conclusion in this study is that the Kado Ragam media can improve learning outcomes of Pancasila Education. Suggestions for further research can create domino card media in other subjects.